(untitled) (Albayan Scientific Journal, 2023)
Extensive co-grazing in the Libyan Al-jabalAlakhdar region is a traditional anthropogenic stress but it has not been systematically evaluated at district level. Land cover of a 90,000 ha study area was mapped by remote sensing and GIS with field survey verification in order to classify land cover, calculate livestock numbers at each unit and evaluate the capacity of each unit. Evaluation of Actual Stocking Rate (ASR) is based on number of livestock, area over which livestock are spread and elevation of its number caused by importing forage. The livestock rates vary geographically so, to calculate a more spatially accurate ASR a raster grid used to give 217 units. The outcomes compared with Government records. Therefore the ASR is organised and presented in terms of frequency distributions for each land cover class. The ASR then adjusted by calculate the mass of supplemental forage which is about 50 kg 100 H-1 day-1 over a three-month period in a year. Calculation of sustainable stocking rate (SSR) depends on required annual biomass intake per animal (R), average fraction of the soil surface covered with annual plant species and edible shrubs (F), averaged palatable biomass after a dry season (P), and X which is a variable that considers both grazing efficiency, as animals do not eat 100% of plants. This study applied three different scenarios to evaluate the factor X. First proposal, the total edible biomass from the sample plots is multiplied by 0.5. Second scenario, X = 0.5 for the annual grass and X = 1 for the shrubs. Third scenario, the value of X is X = 0.5 for the annual grass and adjusted to consider the potential impact of plants palatability. The third scenario gives the best correlation with observed grazing damage at 0.92. The new outcomes has not been attempted elsewhere, new procedure in calculation of ASR and SSR resulted in improved correlation with an index of environmental damage caused by grazing is presented. The biomass from grass decreases as from shrubs increases as the percentage of cover increases the total biomass is approximately constant at about 815 kg ha1.